Radiation and Viscous Dissipation Effects on Laminar Boundary Layer Flow Nanofluid over a Vertical Plate with a Convective Surface Boundary Condition with Suction - K. Gangadhar (Journal of Applied Fluid Mechanics, 2016)
The problem of laminar radiation and viscous dissipation effects on laminar boundary layer flow over a vertical plate with a convective surface boundary condition is studied using different types of nanoparticles. The general governing partial differential equations are transformed into a set of two nonlinear ordinary differential equations using unique similarity transformation. Numerical solutions of the similarity equations are obtained using the Nachtsheim-Swigert Shooting iteration technique along with the fourth order Runga Kutta method. Two different types of nanoparticles copper water nanofluid and alumina water nanofluid are studied. The effects of radiation and viscous dissipation on the heat transfer characteristics are discussed in detail. It is observed that as Radiation parameter increases, temperature decreases for copper water and alumina water nanofluid and the heat transfer coefficient of nanofluids increases with the increase of convective heat transfer parameter for copper water and alumina water nanofluids.